Capturing the forgotten war: carceral spaces and colonial legacies in Cold War Korea. (April 2019) - Nisa, Richard
Abstract: In this paper, I offer a detailed examination of the spaces and practices of detainment used by the United States military and its proxies between 1945 and the armistice that produced a so-called 'end' of the Korean War in 1953. Avoiding the reductive trappings of the Cold War binary, which positions this 'long peace' as a byproduct of two territorial powers struggling for geopolitical control, my chief objective is to explore how the use of carceral infrastructures on the peninsula demonstrates the abundant connections between the brutal imperialism of the Japanese regime, the US military government which ostensibly sought to liberate people from colonial oppression, and the violent police action meant to contain the 'expansive tendencies' of the Communists. I first position this paper relative to geographic scholarship on prisons, focusing on the important links between carceral spaces and state border-making practices. Next, I place the border-making capacities of carceral spaces into conversation with the complexities of empire by briefly describing the Korean prison assemblage under Japanese colonial rule. I then argue that key aspects of the Cold War carceral infrastructure overseen by the US in the wake of World War II are protractions of the often-ruthless violence of Japan's colonial prison system. In the paper's final two sections I outline the prison systems of the U.S military occupation of southern Korea and the subsequent landscape of detention during the Korean War. Though frequently overlooked, I demonstrate here that spaces of military detainment are important contact zones where the racial and the imperial collide, offering historical geographers a suite of crucial sites through which to push back against the Cold War's simplified binary rhetoric. Highlights: Assesses the practice of military detainment through a geographical lens. Focuses historical geographic attention on the spaces of the Korean conflict. Analyses of carceral spaces vital to understanding war and violence. Ties together scholarship on carceral spaces and Cold War geopolitics. Explores relationship between colonial prisons and military prisons.